2021
DOI: 10.3390/microorganisms9050883
|View full text |Cite
|
Sign up to set email alerts
|

Gene–Phenotype Associations Involving Human-Residential Bifidobacteria (HRB) Reveal Significant Species- and Strain-Specificity in Carbohydrate Catabolism

Abstract: Bifidobacteria are among the first colonizers of the human gastrointestinal tract. Different bacterial species use different mechanisms for utilization of various carbon sources in order to establish themselves in the complex microbial ecosystem of the gut. However, these mechanisms still need to be explored. Here, a large gene–phenotype correlation analysis was carried out to explore the metabolic and genetic diversity of bifidobacterial carbohydrate utilization abilities. In this study, we used 21 different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 72 publications
2
7
0
Order By: Relevance
“…The B. adolescentis isolates had a higher number of glycosidases types and genes encoding glycosidases than the B. pseudocatenulatum isolates, indicating a higher capacity of carbohydrate catabolism. This is in line with previous literature 29 . We identified 16 glycosidase genes with differential gene counts between the two species ( p .adj < 0.05, Mann–Whitney test, Fig.…”
Section: Resultssupporting
confidence: 94%
“…The B. adolescentis isolates had a higher number of glycosidases types and genes encoding glycosidases than the B. pseudocatenulatum isolates, indicating a higher capacity of carbohydrate catabolism. This is in line with previous literature 29 . We identified 16 glycosidase genes with differential gene counts between the two species ( p .adj < 0.05, Mann–Whitney test, Fig.…”
Section: Resultssupporting
confidence: 94%
“…However, currently known LAB that can metabolize tryptophan are mainly Limosilactobacillus reuteri , and the metabolic ability of other species is unclear. Previous studies have shown that Bifidobacterium of the same species but from different sources have different abilities to use carbon sources ( Liu et al., 2021 ). Therefore, it is also necessary to investigate whether the isolation source has an impact on the LAB’ capacity to metabolize tryptophan.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Bb. breve exhibited even greater merit due to the presence of four type-gene clusters associated with FOSs degradation, including β-fructofuranosidase-encoding gene [25]. Thus, it can be implied that Bb.…”
Section: Discussionmentioning
confidence: 99%